Pathologic hip fracture in a 4-year-old boy - EROL, BÜLENT (LIPPINCOTT WILLIAMS & WILKINS, 2002)
A 4-year-old boy was transferred from another hospital to the authors' institution for evaluation and treatment of a pathologic fracture of the left femur. The child had a 5-month history of mild limp and pain in his left proximal thigh. He was knocked over by a dog on the day of admission and subsequently was unable to ambulate. The patient was healthy otherwise with no previous injuries, major illnesses, or surgeries. Developmental, social, and family histories were noncontributory. On physical examination, the patient was a healthy appearing boy who reported pain in his left hip region. He was unable to bear weight on his left lower extremity. There was shortening and external rotation of the left lower extremity. The neurovascular examination was normal. Plain radiographs and magnetic resonance imaging (MRI) scans were taken and are shown in Figures 1 through 4.
Keywords: ANEURYSMAL BONE-CYSTS; CHILDREN; SPINE